-7-z=4

Simple and best practice solution for -7-z=4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7-z=4 equation:


Simplifying
-7 + -1z = 4

Solving
-7 + -1z = 4

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + -1z = 4 + 7

Combine like terms: -7 + 7 = 0
0 + -1z = 4 + 7
-1z = 4 + 7

Combine like terms: 4 + 7 = 11
-1z = 11

Divide each side by '-1'.
z = -11

Simplifying
z = -11

See similar equations:

| -8-(-4)+5-1= | | 9y+4=8y-8 | | 9y-4=8y-8 | | 0.08a=72 | | 4t^3-4=0 | | 17-4(3)+4= | | 25a=-3+3a | | 5[8+5(4-2)]= | | (9/z)-(2/z)=21 | | 35000=x-.06x-.0022x-1000-96000 | | 35000=x-.06x-.0022x-1000 | | 3/10a=6 | | 12=r/3 | | 16-2(2)+2= | | 143x^2-1440x+3600=0 | | 176=-4 | | -4-(-2)+5-3= | | 3[4+6(6-3)]= | | -5(3t-4)+4t=7T-3 | | x/3=x/5+3 | | 5x^4+23x^2-42=0 | | k/5+3=6/5 | | log(8)+log(x+9)=log(128) | | 3(x+3)-5=5x-2(-4+x) | | 9x^2-3x+9=0 | | y=3+3sin(3x-7) | | 3m^2-3m-5=0 | | 20=-2/3x | | 0.12(y-5)+0.18y=0.20y-0.03(30) | | 9y=1/5 | | 2a+5a+18=0 | | 0.08(y-8)+0.06y=0.12y-0.01(50) |

Equations solver categories